STRATEGI PEMASARAN PRODUK TABUNGAN HAJI PADA BANK BNI SYARIAH CABANG KALIBATA DALAM MELAYANI PERMINTAAN NASABAH (STUDI PUSTAKA) TAHUN 2017 - Putri Sarirati; Sri Wahyuni (Sekolah Tinggi Manajemen IMMI, 2020)
BNI Syariah’s marketing strategy in marketing the iB Hasanah savings product refers to two patterns of intensification pattern in which these efforts are made to customers who have already used BNI Syariah products, but BNI Syariah sells them to the closest relatives of the customers and the extensification pattern in which these efforts conducted to customers in other banks that also have high potential for funding in BNI Syariah. The application in marketing the product of Tabungan iB Hasanah in general use the marketing mix 4P theory which includes process (process), people (people or marketing target), product (product), price (place), promotion.